Photoreceptor-mediated regulation of the COP1/SPA E3 ubiquitin ligase. (October 2018) - Podolec, Roman; Ulm, Roman
Highlights: The COP1/SPA E3 ubiquitin ligase is a repressor of photomorphogenesis. The COP1/SPA complex targets photomorphogenesis-promoting factors for proteolysis. Active phytochrome, cryptochrome, and UVR8 photoreceptors regulate COP1/SPA activity. Photoreceptors repress COP1/SPA activity through common and distinct mechanisms. Mechanisms include COP1 nuclear exclusion, COP1-SPA separation, and SPA degradation. Abstract : Plants have evolved specific photoreceptors that capture informational cues from sunlight. The phytochrome, cryptochrome, and UVR8 photoreceptors perceive red/far-red, blue/UV-A, and UV-B light, respectively, and control overlapping photomorphogenic responses important for plant growth and development. A major repressor of such photomorphogenic responses is the E3 ubiquitin ligase formed by CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1) and SUPPRESSOR OF PHYA-105 (SPA) proteins, which acts by regulating the stability of photomorphogenesis-promoting transcription factors. The direct interaction of light-activated photoreceptors with the COP1/SPA complex represses its activity via nuclear exclusion of COP1, disruption of the COP1-SPA interaction, and/or SPA protein degradation. This process enables plants to integrate different light signals at the level of the COP1/SPA complex to enact appropriate photomorphogenic responses according to the light environment.